2011
DOI: 10.1074/mcp.m110.002469
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of a Layered Tissue Reveals Unique Glycolytic Specializations of Photoreceptor Cells

Abstract: The retina is a highly ordered tissue whose outermost layers are formed by subcellular compartments of photoreceptors generating light-evoked electrical responses. We studied protein distributions among individual photoreceptor compartments by separating the entire photoreceptor layer of a flat-mounted frozen retina into a series of thin tangential cryosections and analyzing protein compositions of each section by label-free quantitative mass spectrometry. Based on 5038 confidently identified peptides assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 79 publications
(31 reference statements)
6
88
0
1
Order By: Relevance
“…1B). Consistent with this finding, no PKLR was found in a proteomic analysis of rat retina (19). PKM1 is in brain, muscle, and retina, whereas PKM2 is most abundant in retina (Fig.…”
Section: Resultssupporting
confidence: 78%
“…1B). Consistent with this finding, no PKLR was found in a proteomic analysis of rat retina (19). PKM1 is in brain, muscle, and retina, whereas PKM2 is most abundant in retina (Fig.…”
Section: Resultssupporting
confidence: 78%
“…It had been suggested (27) that the pentose phosphate pathway in the rod outer segment could potentially supply all the NADPH reducing equivalents necessary for the reduction of all-trans-retinal to retinol. More recent studies have shown that glucose enters through transporter Glut-1 into the inner segment (28), where it is phosphorylated to glucose-6-phosphate by hexokinases I and II (29). Glucose-6-phosphate can then be utilized through the pentose phosphate pathway to generate NADPH from NADP ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…This method provides a more precise measure of protein relative abundance, because all peptides available are used (40). Intensities of each protein identified were averaged within each treatment group, and fold-changes calculated between groups.…”
Section: Methodsmentioning
confidence: 99%